Comments on “The Effect of Thyroid Nodule Size and Characteristics on the Accuracy of Fine-Needle Aspiration Biopsy and the Risk of Malignancy” - Mustafa Can Şenoymak (Hitit Medical Journal, 2025)
Abstract is not required for a letter to the editor.